Initial experience with high‐volume plasma exchange in patients with acute liver failure. Issue 3 (5th January 2021) - Kim, Ji Eun; Chun, Sejong; Sinn, Dong Hyun; Kim, Nam Joong; Kim, Semi; Kang, Wonseok; Kim, Jong Man; Choi, Gyu‐Seong; Joh, Jae‐Won; Cho, Duck
Abstract: Background/Aims: High‐volume plasma exchange (HVPE), defined as an exchange of 8 to 12 L per day per procedure or 15% of the ideal body weight with fresh frozen plasma, has shown promising results in improving the survival of patients with acute liver failure (ALF). However, clinical evidence is limited. The aim of this study was to report our initial experience using HVPE as a bridge treatment in patients with ALF. Methods: We retrospectively reviewed 32 consecutive patients awaiting liver transplantation (LT) due to ALF between 2013 and 2020 at Samsung Medical Center in Korea. HVPE has been used for patients with ALF since May 2016 at our institution. Results: During the study period, 16 patients received HVPE. After HVPE, coagulopathies (INR, 4.46 [2.32‐6.02] vs 1.48 [1.33‐1.76], P <  .05), total bilirubin (22.6 [9.1‐26.4] vs 8.9 [5.6‐11.3], P <  .05), alanine aminotransferase (506 [341‐1963] vs 120 [88‐315], P <  .05), and ammonia levels (130.6 [123.7‐143.8] vs 98.2 [84.2‐116.5], P <  .05) were improved. Improvement in the hepatic encephalopathy grade was observed in four patients. Among 16 patients who received HVPE, 12 patients were bridged to LT, and three patients recovered spontaneously. The overall survival was 94% and 69%, respectively at 30 days in patients who received and did not receive HVPE ( P =  .068). Among 18 patients with high chronic liver failure‐sequential organ failure assessment scores (≥13), the overall survival was significantly better for those who received HVPE than for those who did not (91% vs 29%, respectively, at 30 days, P <  .05). Conclusions: Our initial clinical experience with HVPE suggests that HVPE can be a viable option in improving the outcomes of patients presenting with ALF.